Employing carbon nanocomposites for the removal of hazardous contaminants from aqueous solution - P. Senthil , Kumar (Malaysian NANO-An International Journal, 2024)
Carbon nanocomposites have captured the curiosity of catalysis research and adsorption studies owing to their extremely small dimensions and shape-dependent chemical and physical properties. Metal nanomaterials and materials made of carbon, including graphene and carbon nanotube-based nanocomposites, displayed exceptional catalytic properties in organic chemical reactions. Carbon nanocomposites made from biomass are a low-cost, developing, and attractive technology for the production of surface-enhanced nanocomposites. For the elimination of all harmful pollutants, including dyes, heavy metals, emerging contaminants, and persistent organic contaminants, -based nanocomposites are utilised. As a result, the demand for carbon nanocomposites has been rising quickly, and the creation of new methods for preparing them deserves particular attention. This short review gives a comprehensive overview of several hazardous substances and their effects on the environment. Additionally, it examines the production, uses, and types of carbon nanocomposites as well as new developments in their capacity to remove organic contaminants from wastewater. In order to simultaneously remove contaminants from industrial effluent and advance the aims of environmentally friendly growth, future research is required. It’s important to find an affordable technique to use carbon nanocomposites in wastewater treatment in large scale.